Effect of post-treatments on cellulose nanocrystal isolated from oil palm empty fruit bunch (OPEFB) / Siti Maisarah Rahim - Rahim, Siti Maisarah (2017)
Cellulose nanocrystal (CNC) was isolated from oil palm empty fruit bunch (OPEFB) using sulfuric acid (H2SO4) hydrolysis with three different posttreatments which were suspension without post-treatment (CNC1), dialyze against water (CNC2) and neutralized with 0.1 M sodium hydroxide (NaOH) solution (CNC3). The percentage yield of CNC1, CNC2 and CNC3 were 71%, 82% and 83% respectively. The characterization of raw OPEFB fiber, bleaching OPEFB fiber and all CNC were carried out by Fourier transform infrared spectroscopy (ATR-FTIR), UV-Vis spectrophotometer (UV-Vis), chroma meter and scanning electron microscopy (SEM). The FTIR result showed that hemicellulose and lignin from raw OPEFB fiber were removed effectively when treated with bleaching pretreatment. The CNC3 has highest percentage transmittance more than 95 % at wavelength 700 nm due to the no residual sulfate content on surface of CNC compared to CNC1 and CNC2. CNC3 has more transparency and more saturated due to the highest lightness (L) and chroma value (C*) that produced smaller particle of diameter size compared to others CNC. The SEM result showed that the CNC3 had shorter size of rod-like shape compared to CNC2. CNC has been well dispersed and more homogeneous isolated when neutralize with NaOH solution since it is simple and efficient method to form CNC.